2018
DOI: 10.1111/dme.13611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depressive disorders in people with Type 2 diabetes: results from the International Prevalence and Treatment of Diabetes and Depression (INTERPRETDD) study, a collaborative study carried out in 14 countries

Abstract: Our international study, the largest of this type ever undertaken, shows that people with diabetes frequently have depressive disorders and also significant levels of depressive symptoms. Our findings indicate that the identification and appropriate care for psychological and psychiatric problems is not the norm and suggest a lack of the comprehensive approach to diabetes management that is needed to improve clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
91
4
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 32 publications
11
91
4
6
Order By: Relevance
“…There is some overlap with the populations in the previous studies as these were conducted in facilities that did not have dedicated NCD clinics, so will have included patients with T2DM. The nding of our study that one-fth of patients with T2DM (18%) suffered from major depression is similar to the ndings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5-33%) (4) however the nding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% (34). The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID (35) and from Ethiopia with a prevalence of 17 % on the Beck Depression Inventory (BDI) (36).…”
Section: Discussionsupporting
confidence: 87%
“…There is some overlap with the populations in the previous studies as these were conducted in facilities that did not have dedicated NCD clinics, so will have included patients with T2DM. The nding of our study that one-fth of patients with T2DM (18%) suffered from major depression is similar to the ndings of a systematic review by Roy and Lloyd where the they found a prevalence of 19.1% (range 6.5-33%) (4) however the nding is considerably higher compared to that of a collaborative study carried out in 14 countries which found a prevalence of 10.6% (34). The rate of major depression in this study is also comparable to rates of depression in studies from Nigeria with a prevalence of 19.4% based on the SCID (35) and from Ethiopia with a prevalence of 17 % on the Beck Depression Inventory (BDI) (36).…”
Section: Discussionsupporting
confidence: 87%
“…Diabetes distress is a common health problem which frequently co-exists with T2DM (Islam et al, 2013;Lloyd et al, 2018;Nanayakkara et al, 2018). The present study highlighted that 22.5% of men and about 55% of women were screened positive for moderate to high DRD on a DDS-17 scale.…”
Section: Discussionmentioning
confidence: 59%
“…Diabetes mellitus (DM) and depression are major global public health problems, and the prevalence rates of both conditions are increasing rapidly [1,2]. It was estimated that in 2019, there are about 463 million patients with DM worldwide, and the figure is predicted to rise to 700 million by 2045 [3].…”
Section: Introductionmentioning
confidence: 99%